Synergy analysis of cyanidin-3-O-glucoside and catechin: absorption, transport and lipid metabolism effects - Liu, Hangyu; Xiang, Tienan; Zang, Qianxi; Liu, Meihong; Wang, Yuying; Yin, Wandi; Liu, Jingsheng (Frontiers in Nutrition, 2025)
Hyperlipidemia represents a global metabolic epidemic with increasing prevalence, profoundly associated with the etiology of cardiovascular and cerebrovascular diseases. This study investigates the therapeutic potential of two widely distributed bioactive polyphenols, Cyanidin-3-O-glucoside (C3G), catechin, and their synergistic combinatorial formation (C3G-catechin) in modulating hyperlipidemia, using complementary in vitro models (Caco-2 monolayer and Caco-2/HepG2 co-culture systems) to simulate intestinal absorption dynamics and lipid metabolic regulation. Our results reveal that the intestinal absorption efficiency follows the order of catechin > C3G-catechin > C3G, primarily mediated through passive diffusion. Furthermore, these polyphenols exhibited significant hypolipidemic effects by downregulating the transcriptional and translational levels of lipid metabolism-related genes, such as SREBP-1, PPARγ, and FAS. This downregulation led to a reduction in key metabolites, including total cholesterol, triglycerides, and LDL-C. Notably, the C3G-catechin combination demonstrated superior regulatory efficacy compared to the individual compounds, suggesting synergistic bioactivity. This study provides mechanistic insights into the enteric transport dynamics and metabolic modulation of dietary polyphenols, highlighting their therapeutic potential to reduce harmful cholesterol level. These findings propose new perspectives for developing nutritional health foods aimed at preventing and treating hyperlipidemia.